Jawabanmu

2014-09-08T17:12:03+07:00
a.       Nilai n P(-1) = 6
(-1)^4 + 3(-1)^3 – 2(-1)^2 + n(-1) + 5 = 6

 1 – 3 – 2 – n + 5 = 6
 -n + 1 = 6
-n = 5
 n = -5  


b.     
Dengan cara horner
      -1  :   1   3   -2   -5       5                      
                                                          0  -1   -2   4       1
    +
                                                

                                                --> 1    2   -4  -1 (hasil bagi)     6
  -> sisa

Jadi, x3 + 2x2 – 4x -1 dengan sisa 6